2011
DOI: 10.1007/s11814-010-0464-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of glucose isomerase activity by pretreatment with substrates prior to immobilization

Abstract: To improve the activity of covalently immobilized glucose isomerase, the effects of glucose isomerase pretreatment with D-glucose or D-xylose prior to immobilization were investigated. Glucose isomerase was pretreated with D-glucose or D-xylose to prevent loss of activity, followed by immobilization on a silica gel surface. Pretreated immobilized glucose isomerase (PIGI) with 2.0 M D-xylose (194.0 U/g matrix) had higher activity than PIGIs with D-glucose. The optimal temperature, reaction time, and agitation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For example, Song and coworkers immobilized S. rubiginosus GI on aminopropylsilane-activated silica gel using glutaraldehyde as a cross-linking agent, resulting in multipoint covalent attachment of the enzyme to the support. 79 The enzyme was immobilized with and without substrate pretreatment, using both D-xylose and D-glucose. After optimizing the pretreatment conditions with regard to time, temperature and agitation, the authors reported that pretreated immobilized GI (PIGI) displayed 2.5 fold higher activity relative to non-pretreated IGI.…”
Section: Methods For Gi Immobilizationmentioning
confidence: 99%
“…For example, Song and coworkers immobilized S. rubiginosus GI on aminopropylsilane-activated silica gel using glutaraldehyde as a cross-linking agent, resulting in multipoint covalent attachment of the enzyme to the support. 79 The enzyme was immobilized with and without substrate pretreatment, using both D-xylose and D-glucose. After optimizing the pretreatment conditions with regard to time, temperature and agitation, the authors reported that pretreated immobilized GI (PIGI) displayed 2.5 fold higher activity relative to non-pretreated IGI.…”
Section: Methods For Gi Immobilizationmentioning
confidence: 99%
“…However, major drawbacks of the process are inactivation of GI at higher temperatures (above 60 °C), narrow pH operation window, inhibition of GI in the presence of Ca 2+ ions (prerequisite for the action of amylase when liquefaction, saccharification, and isomerization are carried out simultaneously), requirement of Co 2+ ions for enzyme activity, and suboptimal concentrations of the product . Notably, the combination of divalent metal ions (e.g., Co, Mn, Mg, and Fe) with the amino-acid compositions of GI (e.g., histidine) can contribute to the improvements in terms of both activity and stability of the enzymes. The immobilization of GI with porous materials (e.g., silica/chitosan hybrid microspheres) can somewhat extend the narrow range of pH (5.8–8.0) and temperature (40–80 °C), but still not widely enough. For these reasons, the enzyme efficiency is still low from an economic point of view, and a large quantity of enzyme is thus needed to obtain viable throughputs. , To overcome these drawbacks, a suitable chemo-catalytic system is thus desirable and the later sections discuss both homogeneous and heterogeneous catalyzed isomerization.…”
Section: Biocatalytic Processesmentioning
confidence: 99%
“…21 Therefore, we attribute increased apparent activity to reduced intrafiber diffusion due to surface enrichment of the enzyme during processing. We also considered additives 56 such as glycerol trehalose, known to improve protein stability, as well as a substrate, 57,58 raffinose, to protect the enzyme from deactivation during immobilization. Using concentrations comparable to these previous studies, the addition of 1 M glycerol in the electrospinning solution resulted in an approximate 2-fold increase in apparent activity when compared to α-gal immobilized in the absence of any additive (Figure 6) similar to previous reports.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%